2015
DOI: 10.1038/mt.2014.176
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity of miR-1280 in Melanoma by Regulation of Src

Abstract: MicroRNAs (miRNAs) play a key role in cancer progression by coordinately repressing target genes involved in cell proliferation, migration, and invasion. miRNAs regulate gene expression by repressing translation or directing sequence-specific degradation of complementary mRNA. Here, we report that expression of miR-1280 is significantly suppressed in human melanoma specimens when compared with nevi, and in human melanoma cell lines when compared with cultured normal human melanocytes. The proto-oncogene Src wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 41 publications
0
11
0
1
Order By: Relevance
“…Many recent studies have reported the expression and role of "miR-1280" in various cancer types (12)(13)(14)(15)(16)(17). In melanoma cells, "miR-1280" displays antitumor activity by regulating the proto-oncogene Src (12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many recent studies have reported the expression and role of "miR-1280" in various cancer types (12)(13)(14)(15)(16)(17). In melanoma cells, "miR-1280" displays antitumor activity by regulating the proto-oncogene Src (12).…”
Section: Introductionmentioning
confidence: 99%
“…Many recent studies have reported the expression and role of "miR-1280" in various cancer types (12)(13)(14)(15)(16)(17). In melanoma cells, "miR-1280" displays antitumor activity by regulating the proto-oncogene Src (12). "miR-1280" can inhibit invasion and metastasis by targeting Rock1 in bladder cancer cells, and the high-miR-1280 bladder cancer group had significantly higher overall survival probability compared with the low-miR-1280 group (13).…”
Section: Introductionmentioning
confidence: 99%
“…tRF/ miR-1280 overexpression leads to suppress proliferation and invasive ability to melanoma cell. all of the above-mentioned data can be suggested that it represents a promising molecular target for anticancer therapy (33). The opposite results in the early stage of primary Non-small Cell Lung Cancer (NSCLC) patients reported that increasing rate of tRF/miR-1280 can inhibit proliferation signaling pathways (34) .…”
Section: Discussionmentioning
confidence: 99%
“…85 For example, Sun et al reported the role of miR-1280 in suppressing melanoma by regulating Src, which acts as proto-oncogenes by mediating tumor proliferation and invasion. 86 Intratumoral injection of miR-1280 complexed with the siPORT transfection reagent significantly suppressed melanoma progression in vivo . Tiwari et al proved that oral squamous cell carcinoma cells with overexpressed miR-125a showed reduced proliferation and invasion since estrogen-related receptor α was significantly downregulated.…”
Section: Mirna-based Therapeutic Strategiesmentioning
confidence: 99%